Tabulations from the 1957 Current Population Survey on Religion: A Contribution to the Demography of American Religion - Mueller, Samuel A. (Journal for the scientific study of religion, 1972)
This paper presents some previously unpublished data from the Current Population Survey's 1957 interview sample on religion. All of the available data from this sample have now been published. Our review of these data indicates that there has been a structural convergence between white Protestants and Catholics, but that the Jews and blacks have not been parties to this convergence. The necessity for future questions on religion on both the monthly Current Population Survey and the decennial census is discussed.